Studi Literatur Pengaruh Media Video Terhadap Keterampilan Praktik Pangkas Rambut - Kharisma Aprodhita Az Zahra Putri Hidayat; Anisa Shinta Dewi; Savia Fitrianing Tyas; Ifa Nurhayati; Anik Maghfiroh (Jurnal Tata Rias, 2024)
The development of digital technology has driven significant changes in learning strategies, particularly in vocational education that emphasizes practical skills. One of the most effective media is instructional video. This study aims to systematically examine the impact of video media on enhancing haircutting practice skills. The research design employed is a literature review with a descriptive qualitative approach. Data were collected through the analysis of ten national and international journals discussing the implementation of video in hairdressing practice education. Data collection techniques involved scientific document searches, inclusion-based selection, content analysis, and thematic synthesis. The findings reveal that video media significantly contributes to improving students’ skills by providing clear visualizations of work procedures, learning time flexibility, and increased motivation. Videos allow learners to revisit materials, understand techniques in depth, and foster independent learning. Furthermore, videos serve as tools for self-evaluation in haircutting practice. However, challenges such as limited devices, internet access, and digital literacy remain issues of concern. Based on these findings, video is recognized as a highly potential learning medium to be implemented in practical skill education, especially in the field of hairdressing.